7, 8-dihydroxyflavone protects 6-OHDA and MPTP induced dopaminergic neurons degeneration through activation of TrkB in rodents. (4th May 2016) - Luo, Dandan; Shi, Ying; Wang, Jun; Lin, Qing; Sun, Yi; Ye, Keqiang; Yan, Qiao; Zhang, Hai
Highlights: 7, 8-DHF alleviated akinesia of 6-OHDA rat model of parkinsonism by protecting dopaminergic neurons. 7, 8-DHF elevated TrkB phosphorylation in the SN in 6-OHDA rat model. 7, 8-DHF protected acute MPTP neurotoxicity in mice. Abstract: Brain-derived neurotrophic factor (BDNF) is a notably important neurotrophin which regulates neuronal survival and differentiation in the nervous system. However, its clinical usage is particularly limited. 7, 8-dihydroxyflavone (7, 8-DHF), which acts as a selective agonist of BDNF receptor TrkB, is reported to possess neuroprotective effects both in vitro and in vivo. Here we explored the potent neuroprotective effects of 7, 8-DHF in 6-OHDA induced rat and MPTP induced mouse model of Parkinsonism. The results demonstrated that treatment with 7, 8-DHF in drinking water for four weeks (two weeks before 6-OHDA + two weeks after 6-OHDA lesion) significantly improved dopamine-mediated behaviors in 6-OHDA rat model, and prevented the loss of dopaminergic neurons in the substantia nigra (SN). Phospho-Y816-TrkB immunostaining showed that TrkB phosphorylation was significantly elevated in the SN in 7, 8-DHF pretreated group, indicating 7, 8-DHF activated TrkB and likely contributed to its neuroprotective effects. 7, 8-DHF also protected acute MPTP neurotoxicity in mice but did not affect the climbing behavior in pole test. Thus our study indicates the neuroprotective properties of 7, 8-DHF through the activation of TrkB, which provides a novel therapeutic treatment for Parkinson's disease.